2017
DOI: 10.1136/bmjsem-2017-000281
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric evaluation of commonly used game-specific skills tests in rugby: A systematic review

Abstract: ObjectivesTo (1) give an overview of commonly used game-specific skills tests in rugby and (2) evaluate available psychometric information of these tests.MethodsThe databases PubMed, MEDLINE CINAHL and Africa Wide information were systematically searched for articles published between January 1995 and March 2017. First, commonly used game-specific skills tests were identified. Second, the available psychometrics of these tests were evaluated and the methodological quality of the studies assessed using the Cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…This was despite the elite players showing better tackling and catching skills. Given the importance of passing in rugby as evidenced by the number of studies investigating the passing ability of RU or RL players,21 these findings probably indicate similar proficiency in passing abilities between elite and subelite U16 RU playing competitive rugby in Zimbabwean schools. Consistently, passing components failed to show discriminative ability between NZ U16 players and SA U16 rugby players 11.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This was despite the elite players showing better tackling and catching skills. Given the importance of passing in rugby as evidenced by the number of studies investigating the passing ability of RU or RL players,21 these findings probably indicate similar proficiency in passing abilities between elite and subelite U16 RU playing competitive rugby in Zimbabwean schools. Consistently, passing components failed to show discriminative ability between NZ U16 players and SA U16 rugby players 11.…”
Section: Discussionmentioning
confidence: 81%
“…Practically, this hints to the coaches the importance of skill training incorporating tackling and catching skills among U16 RU players. A recent review showed that tackling and catching represent important technical elements in rugby and are commonly evaluated among rugby players 21. However, there are limited studies comparing game-specific skills of elite U16 to subelite U16 RU players in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…To test study hypotheses, a cross-sectional design was employed to compare participant performances based on the School Clinical Rugby Measure (SCRuM) test battery. The processes involved in developing the test battery have been explained elsewhere [26][27][28][29][30]. Two hundred and eight (208) schoolboys participated in this study and were derived from three different schools.…”
Section: Study Design Research Setting and Participantsmentioning
confidence: 99%
“…The present study was conducted to evaluate the logical or content validity and the practical feasibility of each test item in the newly-designed SCRuM test battery developed for use in a large study to determine the anthropometric, physical, physiological and rugby-specific game skills discriminating young male adolescent rugby players by playing abilities and level of competition. Briefly, the test battery had been developed from information gathered through a narrative and systematic literature review [ 10 , 11 ] combined with results from a qualitative study investigating the perceptions of local rugby coaches of the qualities important in rugby for young adolescent rugby players and the corresponding tests used for evaluation of these qualities. This study was therefore carried out to refine the first version of the SCRuM test battery by evaluating the relevance, comprehensiveness of the test items included in the test battery based on rugby experts perceptions and further ascertain the practical feasibility of conducting the various test items included in the test battery as judged by the local high school coaches likely to be intended users of the test battery.…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted between January and February 2018. Possible candidate names for international experts were obtained from an online document listing “top” 100 experts in sports science [ 66 ] and also from reference lists of two systematic reviews conducted by the lead author [ 10 , 11 ]. This was done to determine the authors frequently publishing on physical characteristics and rugby-specific game skills.…”
Section: Methodsmentioning
confidence: 99%